2010
DOI: 10.1002/ajim.20866
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study of ulnar neuropathy at the elbow in Washington State workers' compensation

Abstract: Work-related UNE is a common and costly occupational health challenge. Efforts to accurately diagnose UNE and maximize functional recovery should start in the first medical encounter. Older workers, those who have concomitant carpal tunnel syndrome, or who are already receiving wage replacement benefits at the time of diagnosis deserve special attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…In many patients, the progressive disability resulting from ongoing pain, paresthesias, and muscle weakness (6-10) has a considerable economic impact. Juratli et al (11) found that nearly half of all workers with ulnar neuropathy at the elbow were receiving disability benefits prior to their official diagnosis. Cubital tunnel syndrome, therefore, has important functional and financial implications for patients.…”
Section: Introductionmentioning
confidence: 99%
“…In many patients, the progressive disability resulting from ongoing pain, paresthesias, and muscle weakness (6-10) has a considerable economic impact. Juratli et al (11) found that nearly half of all workers with ulnar neuropathy at the elbow were receiving disability benefits prior to their official diagnosis. Cubital tunnel syndrome, therefore, has important functional and financial implications for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective, passive surveillance studies of cubital tunnel syndrome incidence rates have been performed in a small Italian province 3 and in a Workers' Compensation cohort in Washington State 4 . Prospective, active surveillance studies of prevalence rates have only been performed in at-risk occupational cohorts 2,5 .…”
mentioning
confidence: 99%
“…Compression also occurs in the Guyon canal at the wrist. It has proved difficult to estimate incidence and prevalence, but between 1995 and 2000 Juratli et al [59]. reported that 2,863 cases were diagnosed by the Washington State workers compensation system.…”
Section: Ulnar Neuropathymentioning
confidence: 99%